Philip Morris International’s Ethical Dilemma of Child Labor - Tonsi, Azza Asaad (Journal of Economic, Administrative and Legal Sciences, 2020)
Tobacco production is a multi-billion-dollar global industry. Unfortunately, the cultivation of tobacco in some companies engages the labor of children throughout the world in extremely dangerous environments, which has both immediate and long-term consequences for children and society. This paper explores Philip Morris International company's ethical dilemma of child labor and the human rights concerns associated with child labor. The purpose of the following research is to analyze the history of Philip Morris International in regards to child labor in Kazakhstan ,and examining the company's responses and policy implementation. It is the ambition of this research to offer further recommendations to resolve the ethical dilemma. The aim of the research is to emphasize on the importance of health and education for children more than jobs. Also, to show how negative public image can influence the business in different ways, such as stock prices , political influence, sales, and the morale of employees might be affected as well. Although PMI is blamed for its child labor unethical practices, but its social responsibility duties are met. Phillip Morris practice its philanthropic, legal, ethical, and economic responsibilities through various activities. The research also discusses the arguments for and against child labor in Tobacco production. Poverty is the main cause of child labor in agriculture, together with limited access to quality education and access to adult labor, and traditional attitudes towards children’s participation in agricultural activities. The primary research tool was surveys.The survey had fixed sets of questions, which are used to collect quantifiable information. The questions in the survey were yes and no questions. A format of ethical decision making was implemented by answering six test options by a sample size of 30 students. The test options were harm test, publicity test, defensibility test, reversibility test, colleague test, and organization test.Although there have been abounding claims as well as evidence of the abuse of child labor laws in the United States of America, and frequently other countriesthroughout the world; the following research is focused on one country which isKazakhstan.and risks, and traditional attitudes towards children’s participation in agricultural activities.Finally, the research proposes general actions and recommendations to solve this problem. Pillip Morris International had developed a new code of conduct wherever they source Tobacco to show more support against child labor.
Keywords: child employment; ethical dilemma; child labor; Tobacco suppliers; Philip Morris International; whistle blowing; code of conduct